Radiologic Features and Prognosis of Gastric Perforation - Putra, I Putu Aryana Kusuma; Inayah Wulandari; Shira Shalsabina Shafitri (Jurnal Biologi Tropis, 2025)
Gastric perforation carries high rates of morbidity and mortality, making it a critical surgical emergency. This systematic review presents recent evidence of radiological imaging, including its evaluation for the diagnosis of gastric perforation and its effect on patient prognosis. The search strategy included an extensive literature review from online databases, including PubMed and Google Scholar, with key phrases (such as "gastric perforation" and "diagnostic imaging"). A qualitative synthesis was done to evaluate the diagnostics of different imaging techniques and prognostic factors. The most relevant result is that Multidetector Computed Tomography (MDCT) continues to be the golden test, showing 82-90% accuracy in detecting perforation based on identifiable characteristics of the extraluminal free air. In summary, gastric perforation is a life-threatening condition where quick, accurate diagnosis with MDCT is vital for better outcomes, as delays exceeding 24 hours significantly raise mortality risk. This review highlights the importance of integrating MDCT into clinical protocols to speed up diagnosis and treatment, ultimately enhancing patient survival.